1982
DOI: 10.1007/bf00547561
|View full text |Cite
|
Sign up to set email alerts
|

Use of stable labelled carbamazepine to study its kinetics during chronic carbamazepine treatment

Abstract: The kinetics of carbamazepine using stable labelled 15N-carbamazepine was studied in 4 epileptic patients who had been treated with it for at least 6 months. There was a decrease in half-life (12.3 +/- 0.8 h) and an increase in total plasma clearance (58.0 +/- 6.5 ml/min) as compared to single dose studies, which provide further evidence that carbamazepine induces its own metabolism during long-term treatment. Analysis of the urinary metabolites indicated induction of the epoxide-trans-diol pathway. Predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

1983
1983
2000
2000

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 11 publications
1
6
1
Order By: Relevance
“…CBZ is known to induce its own metabolism in a dose-dependent manner (Rapeport et al, 1983). These data also suggest that CBZ-E formation is also induced and this is supported by studies of urinary metabolite excretion (Eichelbaum et al, 1982).…”
Section: Discussionsupporting
confidence: 60%
“…CBZ is known to induce its own metabolism in a dose-dependent manner (Rapeport et al, 1983). These data also suggest that CBZ-E formation is also induced and this is supported by studies of urinary metabolite excretion (Eichelbaum et al, 1982).…”
Section: Discussionsupporting
confidence: 60%
“…Failure to find a correlation between dose and serum levels and between serum levels and clinical response to CBZ or its metabolite may be attributed to marked inter-individual variability in the disposition kinetics of the drug (Eichelbaum et al 1975). The influence of autoinduction, genetic differences, dose, variable absorption, time of sampling and disease state may be other contributing factors (Eichelbaum et al 1975(Eichelbaum et al , 1982Morselli et al 1975;Sanchez et al 1986;Kudriakova et al 1992). In agreement with the present study, Post et al (1983) found that CBZ levels in plasma or in CSF were not related to the degree of antidepressant or anti-manic response.…”
Section: Discussionmentioning
confidence: 88%
“…CBZ is a widely used AED. Although biotransformed via many pathways, the primary route of metabolism is epoxidation to CBZ-E which is the major metabolite of CBZ in monotherapy and polytherapy (Eichelbaum et al, 1982) and may contribute to efficacy. It has equipotent anticonvulsant activity as compared with CBZ in animal models (Frigerio and Morselli, 1975) and has potent therapeutic properties in patients with trigeminal neuralgia (Tomson and Bertilsson, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…It has equipotent anticonvulsant activity as compared with CBZ in animal models (Frigerio and Morselli, 1975) and has potent therapeutic properties in patients with trigeminal neuralgia (Tomson and Bertilsson, 1984). CBZ-E may help explain the difficulty in establishing a dose/ concentration relationship for CBZ (Brodie et al, 1983;Eichelbaum et al, 1982). CBZ-E is less protein bound (5&84%, mean 68%) than the parent CBZ (60-85%, mean 75%) (MacKichan et al, 1981).…”
Section: Discussionmentioning
confidence: 99%